2014
DOI: 10.3790/vjh.83.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Erwerbsminderungsrente in Deutschland – Ein unterschätztes Risiko(?)

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The long-term unemployed were eligible to apply only for a limited time, so they lacked the 5 years of paid contributions and the eligibility to apply for DP. In general, the higher proportion of disabled men in the East was confirmed by previous research (Hagen et al, 2010 ; Hagen & Himmeireicher, 2014 ).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The long-term unemployed were eligible to apply only for a limited time, so they lacked the 5 years of paid contributions and the eligibility to apply for DP. In general, the higher proportion of disabled men in the East was confirmed by previous research (Hagen et al, 2010 ; Hagen & Himmeireicher, 2014 ).…”
Section: Discussionsupporting
confidence: 79%
“…The growing incidence in cardiovascular and musculoskeletal diseases observed among East German men is suggested to be explained by the disproportionate numbers of these men working in manual jobs with stressful environmental conditions (Hagen et al, 2010 ). Previous research has also suggested the high risk of disability due to chronic health problems associated with mental disorders and somatic illnesses in Germany, in general and among people aged 55–60 and men in the East, in particular (Hagen & Himmeireicher, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 80 relevant publications were identified through the REHADAT database and reviewed regarding relevant influencing factors on reduced earning capacity. These publications primarily comprised a reduced number of factors that influence the risk of reduced earning capacity, e.g., health condition, utilization of health services, and motivation to return to work (Briest 2020); a selection of sociodemographic factors (Hagen and Himmelreicher 2014); various health conditions (Roski et al 2017); or an examination of data from the German pension insurance system, which includes, for example, the duration of sickness benefits, receipt of benefits for participation in working life, gender, income, and level of education (Bethge et al 2011). Further publications address the effectiveness of medical and vocational rehabilitation programs (Dannenmaier et al 2020).…”
Section: Designing the Questionnairementioning
confidence: 99%
“…Poverty increased among the disabled and is substantially higher than for individuals without disabilities (Figure 7; Kemptner, 2014), although Figure 7 does not include the steps taken in 2014 to increase disability pension entitlements somewhat (Box 4). Individuals with weak socio-economic background face a higher risk of disability (Hagen and Himmelreicher, 2014). The share of disability benefits recipients with mental illhealth increased substantially in recent years, especially among those aged 55 to 60 (OECD, 2015c).…”
mentioning
confidence: 99%